ISOLASI PERIPHERAL BLOOD MONONUCLEAR CELLS (PBMCS) DARI DARAH MANUSIA SEHAT DENGAN METODE SENTRIFUGASI GRADIEN FICOLL - Warnasih, Siti; Yulia, W; Artika, I. M; Sasmono, R. T. (-)
Peripheral blood sel mononuclear cell (PBMC) is a white blood cell that can be isolated using the gradient centrifugation method. Ficoll is a reactant which can be used in this method because it produce a high viability i.e. 97.1% ± 1.0%. This research aims to isolate PBMC from healthy human blood. PBMC’s result is used for analysis of dengue virus immune response.Dengue viruses infect PBMC, so going on the secretion of cytokine which is one marker of severity of dengue disease. Expression of cytokines can be measured using quantitative real-time reverse transcription – polymerase chain reaction (qRT-PCR).Venous blood from healthy human is takenaseptically using anticoagulants heparin, then PBMC is isolated with ficoll gradient centrifugation method to produce buffy coat that contain PBMC. Viability of PBMC is calculated using hemositometer with the help of a microscope.Based on the results obtained by PBMC isolation per mL of venous blood that is 2, 08x106 up to 2, 61x106 with an average of 2, i.e. 31x106 withviabilityof 95-99%. These results indicate that this method is quite effective in isolating PBMC from healthy human blood.Keyword : blood, ficoll, centrifugasigradien, PBMCs